Electrospinning based fabrication and performance improvement of film electrodes for lithium-ion batteries composed of TiO2 hollow fibers - Yuan, T.; Zhao, B.; Cai, R.; Zhou, Y.; Shao, Zongping (Royal Society of Chemistry, 2011)
Film electrodes composed of 1D TiO2 or TiO2/Ag composite hollow fibers were fabricated by a coaxial electrospinning technique, and were applied as the anode of lithium-ion batteries free of any binder or conductive additive. SEM and TEM characterization demonstrated that uniform hollow fibers with an average outer diameter of around 1.5 μm and wall thickness of around 200 nm were successfully obtained. Ag nanoparticles were dispersed in the TiO2/Ag composite hollow fibers homogeneously. SEM, TEM and BET surface area characterizations demonstrated that the TiO2 and TiO2/Ag hollow fibers have a mesoporous wall structure. Galvanostatic charge and discharge tests demonstrated that the TiO2 film electrode had poor capacity and rate capability by using conventional copper foil as the current collector. The incorporation of silver with the formation of the TiO2/Ag composite electrode was marginal in improving the electrode performance. Modifying the copper foil with silver paste increased the surface roughness obviously, which significantly increased the electrode performance of the TiO2 film electrode with the second discharge capacity reaching 130 mAh g−1 at 1 C rate. The electrode morphology was successfully preserved after 50 electrochemical cycles. Electrospinning is highly promising as a powerful technique for the fabrication of binder and conductive additive-free TiO2 film electrodes for lithium-ion batteries, while increasing the surface roughness of the current collector is critical to achieve high performance.